Pendampingan Penulisan Opini Kritis dan Etika Berkomunikasi di Media Sosial bagi Siswa SMAN 3 Denpasar - Ragil Noviyanti; Asrul Zain Asy'ari; Ibnu Yunianto; Adi Prasetyo; Amalia Hartiningrum; Trias Widha Sari; Athika Dwi Wiji Utami (Jurnal Pengabdian Masyarakat Universitas Darul Ulum, 2026)
This community service research is entitled "Mentoring Critical Opinion Writing and Ethical Communication on Social Media for Students of SMAN 3 Denpasar." The goal is to respond to the phenomenon of intensive social media use that is often not balanced with adequate critical thinking skills and communication ethics. Through structured mentoring, this research aims to improve students' ability to write structured, fact-based, and responsible opinions, while also strengthening ethical awareness when communicating on social media. The method used is a community service approach with a series of activities: socialization, critical opinion writing workshops, ethical social media simulations, and reflections with teachers and students. The results of the implementation show that this mentoring was able to significantly increase students' understanding, as evidenced by the pre-test and post-test questionnaire results which showed a 45% increase in the understanding of social media ethics (from an initial average of 40% to 85%). In addition, this mentoring helped students distinguish facts from opinions, reduce provocative comments, and develop more polite and ethical communication habits in the digital space. This research emphasizes the importance of the role of schools in designing digital literacy and communication ethics mentoring programs so that social media can become an educational space, not just a space for entertainment without reflection. In addition, this mentoring activity also provided students of SMAN 3 Denpasar with the opportunity to participate in a student journalism competition held by Jawa Pos Radar Bali, where they won third place in the hard news category and first place in the feature category.